Law at two speeds: Legal frameworks regulating foreign investment in the global South - Lorenzo Cotula (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
The global legal system regulating foreign investment in lower-income countries is more geared towards enabling secure transnational investment flows than it is towards ensuring that these flows benefit people in recipient countries. There is a need to improve national and international law safeguards for rights that may be affected by investment flows, and to strengthen local capacity to exercise those rights and get a better deal from incoming investment.
Keywords: 330